The Effort Of Improving The Civics Students Achievements In The Effects Of Globalizations By Using Snowball Throwing Method - Suwarto, Heri (LP3 Universitas Negeri Semarang, 2018)
The class action research in concern with the effort of increasing the civics students achievements in the Effects of Globalizations by using Snowball Throwing Method of the students of four grade of SDN Cukilan 03 on 2016-2017 school years is done as the effort to repair the problem of the low achievement and the minimum criteria that is mean 68,00 and only 17 students or 58,6 %Â of 29 students who reach the limit o the minimum criteria. The improving of this studying is held throught the class action research where the teacher as a researcher do this helped by the other teachers and supervisor under the guidance of the competence source. It done into two (siklus). The first (siklus) the improving of the achievement is 31% into 45,5%. In the second (siklus) the increasing of the achievement of the minimum criteria from 58,6% increase to be 72 %. In the second (siklus) the increasing of the avhievement is 12,1% into 80,00 and the increasing of the minimum criteria is from 72 % into 89,7 %. Seeing the final result throught the Snowball ThrowingÂ method, it can be concluded that this method is is proved increasing the achievement and the minimum criteria on the mathematics of the mixing operation of the round number. Based on this research, is suggested to use the Snowball ThrowingÂ method on the civics students achievements in the Effects of Globalizations to make the achievement and the minimum criteria to be more better.